Pengaruh Atribut Produk Dan Gaya Hidup Terhadap Keputusan Perpindahan Merek Pengguna Smartphone Oppo Ke Iphone - Mardianto; Muhamad Stiadi; Hanif Kurniadi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The purpose of this research is to find out the influence of product attributes and lifestyle on the decision to switch from OPPO smartphone users to iPhone. This study is a survey research using a questionnaire as its instrument. The population in this research is consumers using OPPO smartphones who have switched to iPhone in Kolaka Regency, using purposive sampling method, which is a sampling technique with specific criteria. Thus, the sample in this study consists of 100 consumers using OPPO smartphones who have switched to iPhone in Kolaka Regency. The research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis techniques used are measurement model test (outer model) and structural model test (inner model) with Smart PLS 3.0. The results of this study show that there is a positive and significant influence between the variables of Product Attributes on Brand Transfer. This is shown by the Original Sample Estimate value of 0.233 which has a positive effect and the T-Statistic value of 3,171 > 1.64 with a P-Value of 0.001 and significant to Brand Transfer. The results of this study show that there is a positive and significant influence between Lifestyle variables on Brand Transfer. This is shown by the Original Sample Estimate value of 0.688 which has a positive effect and the T-Statistic value of 10,509 > 1.64 with a P-Value of 0.000 and significant to Innovation Capability